PROFIL RESPON MAHASISWA TERHADAP PENGGUNAAN BAHAN AJAR IPA TERPADU TENTANG PENGOLAHAN TEBU SEBAGAI ENERGI TERBARUKAN - Lailatul Nuraini; Supeno Supeno (saintifika, 2017)
Sugarcane is one of the plantation products in the Jember area. Therefore, the processing of sugar cane as renewable energy can be used as a source of learning. The purpose of this research was to describe and analyze student responses profile by using teaching materials about the utilization of sugarcane processing as renewable energy in physics learning. This research method was descriptive research. The research respondents were 30 students who took integrated science course in odd semester 2016/2017 at the Physics Education Study Program, University of Jember. Data collection techniques using student response questionnaires, observation and documentation. Data analysis techniques use percentages. The results of this research indicate that student responses to the use of teaching materials about the utilization of sugarcane processing as renewable energy in physics learning amounted to 83,87% with a very positive category. Based on the analysis, it can be seen that students gave a very positive response using teaching materials about sugarcane processing as renewable energy in physics learning. Thus, the using of teaching materials about sugarcane processing as renewable energy can improve student learning motivation, mastery of concepts, scientific attitudes and environmental awareness.